Effect of carbon nanotube hybrid on the microstructure and properties of AlN skeleton-reinforced highly oriented graphite flake composites. Issue 3 (1st February 2022) - Zhang, Xiaoyu; Zhu, Yuanyuan; Xie, Wenqi; Pang, Haoran; He, Delong; He, Kai; Bai, Jinbo; Shi, Zhongqi
Abstract: AlN skeleton structure-reinforced highly oriented graphite flake (AlN/GF) composites have become a promising candidate for thermal management materials owing to their high thermal conductivity and low thermal expansion. However, the applications of AlN/GF composites are still limited by their poor mechanical properties. Herein, a carbon nanotube-coated alumina (Al2 O3 @CNT) hybrid was used as a reinforcement to improve the mechanical performance of AlN/GF composites prepared via vacuum infiltration followed by spark plasma sintering. It was found that the relative density and orientation degree of the composites decreased slightly with an increase in the Al2 O3 @CNT content from 0 to 2 wt%. However, the fracture toughness and bending strength of the composites improved significantly after the introduction of the Al2 O3 @CNT hybrid reaching up to 1.66 MPa∙m 1/2 and 95 MPa, respectively, which correspond to an improvement of approximately 50% and 20% over those of the AlN/GF composite. With the addition of the Al2 O3 @CNTs, the thermal expansion of the composites increased from 7.3 × 10 -6 /K to ∼15.5 × 10 -6 /K, while the thermal conductivity decreased from 442 to ∼253 W/m/K. The toughening and strengthening mechanisms as well as the thermal impact mechanism of the composites were also investigated.